Propuesta de un manual de funciones, valuación de puestos por puntos y evaluación de desempeño para la empresa “Rento Uno” de la ciudad de Loja - López Ordóñez, Mayra Elizabeth (2015)
This research has the general objective PROPOSE A Function Manual, VALUATION OF POSITIONS FOR POINTS AND PERFORMANCE EVALUATION OF THE COMPANY "RENT ONE" CITY OF LOJA Through the development of this work, it was known and assigned tasks and functions within the company organized a fair and equal manner. For it was examined whether each employee knew what their functions, if the company had Function Manual and if it was applied performance evaluation Thus, it was found that the company "Rento One" do not know if the company has Mission, Vision and Policy plus an Organizational Structural, also said he does not know if it has a manual functions, but it was found that the Most of his staff believes it is important the design of this manual. As for the posts and functions given in each of these a valuation of posts held by points for which the factors object of valuation such as knowledge, skills, responsibility, effort and working conditions was first established, then it determined grades for each factor, the weighting factors was performed giving 40% Knowledge, Responsibility 30% Effort 20% Working conditions 10%, followed by points for grades was fixed and were scored each one of the existing positions in the company making a sum of each job and the manager was obtained reached 285 points, 160 points Secretary, Concierge 100 points, 165 points Guardian, Chief Administrative 225 points, 210 points Accountant, Accounting Assistant 190 points Head of operations 200 points, 255 points Chauffeur, Mechanic 235 points, 220 points mechanical assistant, sales manager seller 235 points and 170 points, tabulated and mathematical formulas applied and finally the graphic was performed to carry out the adjustment Salary according to the functions, knowledge, experience, initiative, personal responsibility, responsibility for team effort and risks in the workplace, resulting in need wage adjustment positions Assistant mechanics and driver with increased 1.43 %. Once the performance evaluation it was known that most of the employees have excellent rating as 96.89 Manager, Secretary 89.6, 45.43 concierge, Guardian 51.26, 93.76 Administrative Officer, Counter 85.42, Accounting Assistant 87.51, COO 100 Driver 84.4, 84.4 Mechanical, mechanical Assistant 60.40 (Regular); 100 Sales Manager, Sales 84.40, with an overall average of 87.19 points equivalent to outstanding, being of great importance for the proper development and development of the activities of "Rented One"